Mammoth and musk ox ESR‐dated to the Early Midlandian at Aghnadarragh, County Antrim, Northern Ireland, and the age of the Fermanagh Stadial. (12th March 2015) - Lister, Adrian M.; Grün, Rainer; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> The Aghnadarragh site presents the most complete known Midlandian (last cold stage) sequence in Ireland. Above a glacial till and below organic deposits of the Aghnadarragh Interstadial, a unit of poorly sorted gravel and diamicton yielded numerous fossils of woolly mammoth and rarer musk ox, the first record of that species in Ireland. The mammoth molars are of relatively small size and distinctive morphology that probably relate to local environmental conditions. Dating of three mammoth molars by Electron‐Spin‐Resonance indicates an age for the faunal horizon in the range 109 to 74 ka, corresponding to the later part of MIS 5, presumably MIS 5d or 5b in view of the cold‐adapted flora and fauna, or possibly early MIS 4. This in turn suggests that the underlying glacigenic deposits, assigned to the Fermanagh Stadial, formed during a cold stage preceding the last interglacial, rather than being early Midlandian in age as generally assumed. Copyright © 2015 John Wiley & Sons, Ltd.